Democracy’s Achilles Heel or, How to Win an Election without Really Trying. - Collier, P; Hoeffler, A (CSAE (University of Oxford), 2009)
In this paper we investigate the efficacy of illicit electoral tactics and the characteristics which make a society prone to such tactics. We first investigate the chances of an incumbent head of government winning an election. We find that in those elections in which illicit tactics were prevalent the chances of incumbent victory increase substantially, more than doubling the expected duration in office. Further, illicit tactics sharply reduce the importance of good economic performance for survival in office. We then investigate what makes a society prone to illicit electoral tactics. Both structural conditions and institutions matter. Societies that are small, low-income, and resource-rich have little chance of a clean election unless these conditions are offset by checks and balances such as veto points and a free press. Aid has offsetting effects, the net effect being modest. We show that these results are robust to different measures of the conduct of elections and to fixed effects. Finally, we revisit the Jones-Olken result that individual leaders matter for economic performance and find that it holds only where leaders are not disciplined by well-conducted elections.